P13.03 Targeted primary health care and sexual health services can deliver the hepatitis c strategy: one year of fibroscans at the kirketon road centre (krc). (13th September 2015) - Gilliver, R; Scholey, K; Chronister, K; van Beek, I; Read, P
Abstract : Introduction: National and NSW Hepatitis C (HCV) strategies identify primary health care and sexual health services as crucial for expanded assessment and treatment of HCV. KRC is a targeted primary health care facility in Sydney's Kings Cross, involved in the prevention, treatment and care of HIV, STIs and viral hepatitis to people who inject drugs. Since April 2014 KRC has used a portable fibroscan on site and at outreach clinics held at The Langton Centre (drug and alcohol service), NSW Users and AIDS Association, the Medically Supervised Injecting Centre, and the Sydney Sexual Health Centre to assess clients for liver disease. The aim of this study was to describe clients receiving a fibroscan during the first year, their fibroscan results and retention in care. Methods: All clients who underwent a fibroscan from April 2014 through March 2015 were included. Clients' demographics, fibroscan results, HCV genotype, HIV co-infection and follow-up data were analysed. Results: Fibroscans were performed among 161 clients: 106 male, 51 female, 4 transgender. Median age was 43, and 12 (7%) identified as Aboriginal; 146 (91%) reported having injected drugs; 72% (n = 116) were HCV PCR positive (58% genotype 1, 38% genotype 3; 7 were HIV co-infected); 17 were hepatitis B sAg positive (1 HIV co-infected); 28 were of unknown status. Fibroscans showed F0–1 liver fibrosis in 105 (65%), F2 = 28(17%), F3 = 16(10%) and F4 = 12(8%). Follow-up occurred in 122(76%), clients including 26/28 with F3–4 fibrosis. Thirteen clients were able to access clinical trials of HCV treatment. Conclusion: This study demonstrates the utility of delivering a fibroscan service by a health facility that focusses on STIs, HIV and hepatitis. Uptake and retention in care was achieved for this marginalised population. The Hepatitis C strategies' focus on primary health care and sexual health services for HCV care and treatment in an era of interferon-free therapy appears feasible. Disclosure of interest statement: No conflicts of interest to declare.